2005
DOI: 10.1115/1.1812321
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Novel Secondary Flow Feature in a Turbine Cascade With End Wall Profiling

Abstract: A novel secondary flow feature, previously unreported for turbine blading as far as the authors are aware, has been discovered. It has been found that it is possible to separate part of the inlet boundary layer on the blade row end wall as it is being over-turned and rolled up into the passage vortex. This flow feature has been discovered during a continuing investigation into the aerodynamic effects of non-axisymmetric end wall profiling. Previous work, using the low speed linear cascade at Durham University,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Durham cascade has been used extensively in the past for studying secondary flow loss generation and optimization of enwall geometry for loss reduction, and also as a standard test case for validating turbomachinery CFD methods [29][30][31][32]. At the experimental conditions with a Reynolds number of 4x10 5 , the flow in the blade passage is shown to be transitional subject to a bubble type separation on suction surface [30].…”
Section: Durham Turbine Cascade and Rans Turbulent Flow Solutionsmentioning
confidence: 99%
“…Durham cascade has been used extensively in the past for studying secondary flow loss generation and optimization of enwall geometry for loss reduction, and also as a standard test case for validating turbomachinery CFD methods [29][30][31][32]. At the experimental conditions with a Reynolds number of 4x10 5 , the flow in the blade passage is shown to be transitional subject to a bubble type separation on suction surface [30].…”
Section: Durham Turbine Cascade and Rans Turbulent Flow Solutionsmentioning
confidence: 99%
“…The vortex was not significantly weakened, but its migration across the passage towards the suction surface was partially blocked. Similar research on end wall profiling was carried out by Gregory-Smith et al [4] , Ingram et al [5,6] . Weiss and Fottner [7] have done experiments on the influence of load distribution on secondary flows in a straight turbine cascade.…”
Section: Introductionmentioning
confidence: 77%
“…However, the lack of correlation between secondary kinetic energy and total loss is reported by Denton and Pullan (2012) . Ingram et al (2005) also demonstrated that a blade designed with a reduced level of secondary kinetic energy can still increase loss. The relation between loss generation rate and Reynolds stresses has been experimentally investigated by MacIsaac et al (2012) .…”
Section: Othersmentioning
confidence: 93%